Graphene nanoribbons are internalized by human primary immune cell subpopulations maintaining a safety profile: A high-dimensional pilot study by single-cell mass cytometry - Fuoco, Claudia; Luan, Xiangfeng; Fusco, Laura; Riccio, Federica; Giuliani, Giulio; Lin, Hazel; Orecchioni, Marco; Martin, Cristina; Cesareni, Gianni; Feng, Xinliang; Mai, Yiyong; Bianco, Alberto; et al. (Applied Materials Today, 2022)
Graphene nanoribbons (GNRs) are emerging graphene materials showing clear promising applications in the biomedical field. The evaluation of GNR biocompatibility at the immune level is a critical aspect of their clinical translation. Here, we report the ex vivo immune profiling and tracking of GNRs at the single-cell level on eight human blood immune cell subpopulations. We selected ultra-small (GNRs-I-US) and small GNRs (GNRs-I-S), with an average length of 7.5 and 60 nm, respectively. GNRs were functionalized with 115In to trace their cell interactions by single-cell mass cytometry. Both materials are highly biocompatible and internalized by immune cells without inducing significant functional changes. GNRs-I-US interacted to a greater extent with myeloid dendritic cells (mDCs) and classical monocytes, while GNRs-I-S mainly interacted with mDCs. These results demonstrate that structurally precise GNRs are efficiently internalized by immune cells. In addition, our chemical and methodological single-cell approach can be applied to other cell types using various carbon-based nanomaterials, bringing new insights into their safety and future biomedical applications.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Biocompatibility; CyTOF; Immune system; Nanomedicine; Two-dimensional materials